Developing a mechanistic understanding of the nonlinear pharmacokinetics of letermovir and prospective drug interaction with everolimus using physiological‐based pharmacokinetic modeling - Karsten Menzel; Yuhsin Kuo; Dapeng Chen; Georgy Hartmann; Ying‐Hong Wang; Carolyn R. Cho; Jacqueline B. McCrea; Kazuhiko Asari (Wiley, 2023)
Abstract Letermovir is approved for use in cytomegalovirus‐seropositive hematopoietic stem cell transplant recipients and is investigated in other transplant settings. Nonlinear pharmacokinetics (PKs) were observed in clinical studies after intravenous and oral dosing across a wide dose range, including the efficacious doses of 240 and 480 mg. A physiologically‐based PK (PBPK) model for letermovir was built to develop a plausible explanation for the nonlinear PKs observed in clinical studies. In vitro studies suggested that letermovir elimination and distribution are mediated by saturable uridine glucuronosyltransferases (UGT)‐metabolism and by saturable hepatic uptake via organic anion‐transporting polypeptides (OATP) 1B. A sensitivity analysis of parameters describing the metabolism and distribution mechanisms indicated that the greater than dose‐proportional increase in letermovir exposure is best described by a saturable OATP1B‐mediated transport. This PBPK model was further used to evaluate the drug interaction potential between letermovir and everolimus, an immunosuppressant that may be co‐administered with letermovir depending on regions. Because letermovir inhibits cytochrome P450 (CYP) 3A and everolimus is a known CYP3A substrate, an interaction when concomitantly administered is anticipated. The drug-drug interaction simulation confirmed that letermovir will likely increase everolimus are under the curve by 2.5‐fold, consistent with the moderate increase in exposure observed with midazolam in the clinic. The output highlights the importance of drug monitoring, which is common clinical practice for everolimus to maintain safe and efficacious drug concentrations in the targeted patient population when concomitantly administered with letermovir.